Pengaruh Kepemilikan Manajerial, Keputusan Investasi, Keputusan Pendanaan, dan Kebijakan Deviden terhadap Nilai Perusahaan - Aris Sasurya; Nadia Asandimitra (Universitas Negeri Surabaya, 2018)
The main objective of this research is to examine theeffect of manajerial ownership, investment decision, funding decision, and dividend policy on firm value that listed on Indonesia Stock Exchange (IDX). In this study, firm value measured by Price Book Value (PBV). Samples used in this study consisted of 11 companies. This study used a purposive sampling method is by determining the number of samples taken to certain criteria. The data analysis technique used in this study is multiple linear regression analysis which previously has been tested with the classical assumption test. The results showed that simultaneously managerial ownership, investment decisions, funding decisions, and dividend significantly influence on firm value in the companies listed in Indonesia Stock Exchange. Partially managerial ownership and funding decisions does not affect on firm value in the companies listed in Indonesia Stock Exchange, while investment decisions and dividend policy positive effect on firm value in the Companies listed in Indonesia Stock Exchange